Analisis Pengembangan Padi IP 400 Berbasis Pupuk Organik di Kabupaten Trenggalek - Ernawati, Yuyun; Supriyono, Supriyono; Mulyaningtyas, Ratna Dewi (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
The agricultural sector, especially rice commodities, is one of the strategic sectors. Trenggalek Regency has potention in the agricultural sector, especially lowland rice because the majority of its people depend on the agricultural sector for their livelihoods, especially rice commodities and the availability of organic materials. People's dependence on the staple food rice is very high, so need to increase the productivity. One effort that can be made is to intensify the rice planting index, including the rice planting index 400 (IP Padi 400) by using organic fertilizer. This research method is a qualitative method, which was carried out in the Trenggalek District and Gandusari District Farmer Groups in Trenggalek Regency. The results of potention for developing IP 400 rice based on organic fertilizer consists of : human resources, natural resources, social, financial, physical, institutional and spiritual. IP 400 rice development process based on organic fertilizer use a number of strategic steps consist of : using superior varieties (VUG), varietal rotation, seeding technique â€œculikanâ€ or â€œdapogâ€, Irrigation must be available throughout the year, organic fertilization, early monitoring of plant pests and diseases and use of agricultural machinery. The development of organic fertilizer-based IP 400 rice has had an impact on farmers' productivity and income